Effect of PV material, texturing, orientation and tracking on glare impact: A simulation study from an Indian airport - Sreenath, S.; Sudhakar, K.; Ahmad Fitri, Yusop (Elsevier Ltd, 2021)
There is a growing interest in airport-based solar PV systems. At the same time, there is the possibility of glare from the solar PV array, which is a potential aviation safety issue. This paper's main objective is to estimate the technical solar power potential of an airport and assess glare impact for six different scenarios of PV array. These configurations are smooth glass, smooth glass with Anti-Reflective Coating (ARC), light-textured glass with ARC, a variation of tilt & orientation angle, single-axis tracking, and dual-axis tracking. The potential for a land-based solar PV system is assessed based on vacant area and glare impact. The details of the airport site, solar PV array, and the position of observers are provided for software simulation. The occurrence and duration of glare for each scenario are simulated using ForgeSolar software. The impact of glare is assessed based on a standard set by the Federal Aviation Administration (FAA). The technical potential of solar PV in the selected airport is estimated at 9.8 MW. Among the studied scenarios, the safe value of glare is obtained in Scenario 4 (variation of tilt & orientation angle) and Scenario 5 (single-axis tracking). In Scenario 4120 configurations of tilt and orientation angle adhered to FAA's solar glare policy. It is observed that the variation of tilt and orientation angle resulted in zero minutes of glare in several configurations. However, the energy output of the solar PV array was affected. The single-axis tracking solar PV system is expected to generate 35% higher electricity than the fixed-tilt system. Hence, it is concluded that Scenario 5 is the desired arrangement in terms of glare mitigation and energy output. This work will benefit aviation stakeholders for assessing the solar power potential and deciding suitable glare mitigation measures.